2017
DOI: 10.13057/nusbiosci/n090203
|View full text |Cite
|
Sign up to set email alerts
|

Response of soybean genotypes to salinity in germination stage

Abstract: Abstract. Kuntyastuti H, Sutrisno. 2017. Effect of manure, Phosphate Solubilizing Bacteria, and chemical fertilizer application on the growth and yield of soybean. Nusantara . This study aimed to determine the dosages of organic, chemical and biological fertilizers for optimum growth and yield of soybean grown in acidic dryland. Treatments applied were twelve combinations of inorganic fertilizer, phosphate solubilizing bacteria (PSB), and manure. These treatments were arranged in a randomized block design, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The early germination of large seeds could elevate competing capacity with the surrounding weeds and efficient uptake of the resources. The detrimental impacts of high levels of NaCl are in line with earlier observations in soybean by Putri et al (2017) and Yin et al (2022).…”
Section: Germination Testsupporting
confidence: 89%
“…The early germination of large seeds could elevate competing capacity with the surrounding weeds and efficient uptake of the resources. The detrimental impacts of high levels of NaCl are in line with earlier observations in soybean by Putri et al (2017) and Yin et al (2022).…”
Section: Germination Testsupporting
confidence: 89%
“…Several authors have confirmed that the germination potential of soybean seeds reduces in response to salinity, and variations have been seen between genotype responses. Similar to the study conducted by Putri et al (2017) on 16 soybean genotypes (Detam 2, Detam 3, Detam 4, Pangrango, Ijen, Mahameru, Baluran, Petek, G100H, Kaba, Ichiyou, IAC100, Argopuro, Gumitir, Seulawah, and Merbabu), and that of Begum et al (2022) with four genotypes (PI408105A (PI5A), PI567731 (PI31), PI567690 (PI90), and PI416937 (PI37)) under saline stress ranging from 0 mM NaCl to 150 mM NaCl. The reduction in germination in response to osmotic stress occurs because of a deficit in water and the effects of an accumulation of toxic ions that interfere with the absorption of nutrients and cause cytotoxicity and reductions in cell division and embryo development (Taiz et al, 2017;Silva et al, 2019).…”
Section: Resultssupporting
confidence: 53%
“…China is one of the largest soybean consumers in the world, and its import volume increases every year; therefore, it has an urgent need to increase its domestic soybean production [4]. Salinity is one of the main forms of abiotic stress and one of the most common agricultural problems in arid and semi-arid regions [5,6]. Salinity monitoring agencies such as the United States Salinity Laboratory (USSL) found that approximately 1 billion hectares of land out of the 13 billion hectares in the world are affected by salt, according to data from the Food and Agriculture Organization (FAO) of the United Nations [7].…”
Section: Introductionmentioning
confidence: 99%